CONTENT-BASED SYLLABUS - Kaveh Jalilzadeh; Atefeh Tahmasebi (European Scientific Journal, ESJ, 2014)
There is growing interest in a model of language education that integrates language ad content instruction in EFL/ESL classroom. The current paper looks at content-based syllabus, with content (subject matter) providing the point of departure for it. Influences leading to the emergence of content-based instruction are discussed, followed by a brief description of the syllabus as well as the relevant frameworks for organizing and integrating. The paper then deals with several rationales for the integration of language and content. Next, some techniques, strategies, and activities used in implementing content-based syllabus are briefly mentioned. It is also suggested that pre-service and in-service teacher education can benefit from a focus on language and content integration. Some advantages and disadvantages of the syllabus are discussed at the end.